Job satisfaction among Syrian healthcare workers in refugee health centres - Monica Zikusooka; Omur Cinar Elci; Habibe Özdemir (BMC, 2021)
Abstract Background Achieving universal health coverage is subject to the availability, accessibility, acceptability, and quality of health workers. Countries that host refugees and migrants, such as Turkey, must strengthen the capacity of their health systems to increase access to services, especially for refugees and migrants. The Turkish Ministry of Health adapted Syrian refugee healthcare workers in the healthcare services to boost Syrian refugees' access to healthcare. This study aimed to assess job satisfaction and the factors influencing job satisfaction among refugee physicians and nurses working in Refugee Healthcentres (RHCs) in Turkey. Methods A self-administered, cross-sectional survey targeted all Syrian physicians and nurses working in RHCs across Turkey. The short-form Minnesota Satisfaction Questionnaire(MSQ) was used to assess job satisfaction. In total, 555 nurse/midwives and 336 physicians responded, yielding a total response rate of 56.5%. Descriptive analyses and linear regression tests were conducted to determine the level of job satisfaction and to analyze determinant factors. Results Nurses/midwives reported the highest level of general job satisfaction, followed by specialist physicians and general physicians. Physicians who had worked as specialists in Syria but were now working as general physicians in Turkey had the lowest job satisfaction levels. Multiple regression analysis showed that professional status in Turkey, income, teamwork and team management were significantly associated with job satisfaction. Conclusions To maintain a high level of job satisfaction in refugee healthcare workers, human resources management should consider matching job placements with training specialization and support good leadership and good teamwork. Remuneration that accounts for the cost of living and non-financial incentives could also play a significant role in job satisfaction.